PERILAKU SEKSUAL PRANIKAH DALAM PERGAULAN BEBAS REMAJA DARI PRESPEKTIF HUKUM POSITIF DI INDONESIA - Ida, Orintina Vavinta; Suryawati, Nani (Yustitia, 2024)
Premarital sexual behavior is an unnatural phenomenon that often occurs in the life of modern society. Premarital sex is a sexual relationship that is carried out without a legal marriage bond, it often occurs among adolescents so that it becomes a problem in the association of adolescents that is increasingly clear in the community. So that it becomes a serious problem related to social, legal, religious quality that sooner or later will bring the country, especially the younger generation, to the gate of destruction. Normative juridical research or often referred to as doctrinal research is also called library research or document study, because this research is carried out only in written regulations or other legal materials. Based on the results of research according to positive law, premarital sexual behavior is a deviant act and violates social and religious norms in public life in Indonesia, perpetrators of premarital sexual behavior in adolescent associations cannot be charged in the law because it is done consensually. Therefore, the Government and related institutions are trying to conduct socialization to take firm steps to overcome the problem of adolescent promiscuity and premarital sexual behavior.